Survival of patients with malignant neoplastic wound served at a Cancer Center (Research, Society and Development, 2023)
Objective: To evaluate the survival of patients with malignant neoplastic wound treated at a Cancer Center. Method: This is an observational, retrospective and descriptive cohort study, with a quantitative approach, using secondary data extracted from medical records of patients diagnosed with cancer who had a malignant neoplastic wound. Data collection was carried out between 2018 and 2020. For the analysis of quantitative variables, absolute and relative frequencies were considered. To determine the probability of survival, the Kaplan-Meier estimator was used. The log-rank test was used to determine the existence of differences between the survival curves. Results and discussion: The sample consisted of 118 patients. Among the participants, the majority were women, white, married, aged over 60 years, who had completed higher education, attended by the health insurance. There was a predominance of patients diagnosed with breast and head and neck cancer, with advanced staging. The mean overall survival of the sample was 10 months. The probability of overall survival at 1 year was 20%, and at 2 years it was 9%. Smoking history was statistically significant (p=0.05), showing that participants who never smoked had a longer overall survival. The treatment scheme was statistically significant (p=0.005), showing that participants who received the combination of radiotherapy and chemotherapy had a longer survival. Conclusion: The overall survival of patients with a malignant neoplastic wound was eight months, with worse results for patients with a history of smoking and better results for combined treatments.